2015
DOI: 10.1021/acs.langmuir.5b02362
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Amnion-Based Scaffolds as a Barrier Membrane for Guided Bone Regeneration

Abstract: Guided bone regeneration is a new concept of large bone defect therapy, which employs a barrier membrane to afford a protected room for osteogenesis and prevent the invasion of fibroblasts. In this study, we developed a novel barrier membrane made from lyophilized multilayered acellular human amnion membranes (AHAM). After decellularization, the AHAM preserved the structural and biomechanical integrity of the amnion extracellular matrix (ECM). The AHAM also showed minimal toxic effects when cocultured with mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…In examined cases in the present study, it was observed that using dHACM for the reconstruction of mandibular bone defects enhanced osseointegration and provided solid protection against fibrous tissue invasion between the bone graft and host mandible bone. Similar results have also been previously reported (5155). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In examined cases in the present study, it was observed that using dHACM for the reconstruction of mandibular bone defects enhanced osseointegration and provided solid protection against fibrous tissue invasion between the bone graft and host mandible bone. Similar results have also been previously reported (5155). …”
Section: Discussionsupporting
confidence: 93%
“…Following the decellularization of the dHACM, the majority of the growth factors and cytokines, and the structural and mechanical properties were preserved. In addition, dHACM is easy to prepare and handle, and by its use, fibrous tissue invasion can be prevented (51,56). …”
Section: Discussionmentioning
confidence: 99%
“…The fetal membranes have been used in regenerative medicine for nearly a century—long before the term “regenerative medicine” was coined . It is now clear that new uses for the fetal membranes, as well as the stem and stem‐like cells derived from the membranes, are being discovered.…”
Section: Resultsmentioning
confidence: 99%
“…Other types of collagen membranes have been derived from human pericardium and dura mater . There have also been attempts to use the human amnion membranes for making biocompatible membranes using decellularization and sterilization techniques . Lyophilized multilayered amniotic membrane preserves the structural and mechanical properties of the amnion ECM and has good flexibility in adjusting the thickness and mechanical properties.…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%
“…Lyophilized multilayered amniotic membrane preserves the structural and mechanical properties of the amnion ECM and has good flexibility in adjusting the thickness and mechanical properties. This particular membrane has been suggested to promote bone growth whilst limiting fibrous tissue invasion .…”
Section: Membrane Properties and Their Modificationsmentioning
confidence: 99%